Translational delivery of Cool Little Kids to prevent child internalising problems: Randomised controlled trial. (February 2018) - Bayer, Jordana K; Beatson, Ruth; Bretherton, Lesley; Hiscock, Harriet; Wake, Melissa; Gilbertson, Tamsyn; Mihalopoulos, Cathrine; Prendergast, Luke A; Rapee, Ronald M
Objective: To determine whether a population-delivered parenting programme assists in preventing internalising problems at school entry for preschool children at-risk with temperamental inhibition. Methods: Design : a randomised controlled trial was used. Setting : the setting was 307 preschool services across eight socioeconomically diverse government areas in Melbourne, Australia. Participants : a total of 545 parents of inhibited 4-year-old children: 498 retained at 1-year follow up. Early intervention : Cool Little Kids parenting group programme was implemented. Primary outcomes : the primary outcomes were child DSM-IV anxiety disorders (assessor blind) and internalising problems. Secondary outcomes : the secondary outcomes were parenting practices and parent mental health. Results: At 1-year follow up (mean (standard deviation) age = 5.8 (0.4) years), there was little difference in anxiety disorders between the intervention and control arms (44.2% vs 50.2%; adjusted odds ratio = 0.86, 95% confidence interval = [0.60, 1.25], p = 0.427). Internalising problems were reduced in the intervention arm (Strengths and Difficulties Questionnaire: abnormal – 24.2% vs 33.0%; adjusted odds ratio = 0.56, 95% confidence interval = [0.35, 0.89], p = 0.014; symptoms – mean (standard deviation) = 2.5 (2.0) vs 2.9 (2.2); adjusted mean difference = –0.47, 95% confidence interval = [–0.81, –0.13], p = 0.006). Parents' participation in the intervention was modest (29.4% attended most groups, 20.5% used skills most of the time during the year). A priori interaction tests suggested that for children with anxious parents, the intervention reduced anxiety disorders and internalising symptoms after 1 year. Conclusion: Offering Cool Little Kids across the population for inhibited preschoolers does not impact population outcomes after 1 year. Effects may be emerging for inhibited children at highest risk with parent anxiety. Trial outcomes will continue into mid-childhood.